Recent Advances in Graphene‐Based Membranes with Nanochannels and Nanopores - Tongxi Lin; Xinyue Wen; Xiaojun Ren; Vanesa Quintano; Daria V. Andreeva; Kostya S. Novoselov; Rakesh Joshi (Small Structures)
Understating the mass transport via nanopores and nanochannels plays a vital role in membrane‐based separation systems and applications. Graphene and its derivates, such as graphene oxide (GO) and reduced GO, are one‐atom‐thick, 2D materials that exhibit outstanding physical and chemical properties. Based on their fascinating features, graphene‐based materials have become important building blocks for 2D separation membranes that with well‐defined nanopores or nanochannels. In this review, the mass transport through in‐plane nanopores on nanoporous graphene membranes and 2D nanochannels in GO‐based laminar membranes are discussed. The recent advances in nanoporous graphene engineering, as well as separation applications, are discussed. The discussion of GO‐based membranes is unfolded from the structure and properties of GO and nanochannels formed by GO laminates. Through the understanding of GO‐based membrane structures and separation performance, the mechanisms of mass transport in the nanochannels of GO‐based membranes are revealed, and strategies for GO membrane modification are introduced and summarized from both mechanism and application perspectives. This study may provide a highly desirable guideline for future graphene‐based nanostructures and their applications in mass transport.